PENINGKATKAN KOMPETENSI AKADEMIK MAHASISWA MELALUI PELATIHAN PENULISAN ARTIKEL ILMIAH BERBASIS IMRAD - Febrina Nur Ramadhani; Andi Muhammad Syukur Hidayatullah; Lukman Dahlan; Nur Alim Bahri; Wina Ayudia Akbar (Jurnal Abdi Insani, 2025)
The ability to write scientific articles is an essential competency for students to develop academic capacity, enhance scientific literacy, and foster critical as well as systematic thinking skills. However, preliminary surveys indicated that most students of the Faculty of Economics and Business, Universitas Negeri Makassar, still encountered difficulties in preparing scientific articles properly. This community service activity aimed to improve students’ understanding and writing skills through training based on the IMRAD structure (Introduction, Method, Result, and Discussion). The program was conducted over eight weeks using a participatory approach, consisting of four main stages: material delivery, article drafting assistance, manuscript review, and selection of articles for publication. Evaluation was carried out through pre-test and post-test questionnaires and writing skill assessments using a 1–5 scale. The results showed significant improvement in students’ understanding and writing ability, with average scores categorized as good to very good. Participants became more skilled in composing the results, discussion, and conclusion sections, as reflected in the consistent increase in evaluation scores. As a tangible output, two student articles were successfully published, one in a national journal and another in the proceedings of an international conference. These findings indicate that IMRAD-based training is effective in enhancing students’ academic competencies and producing publishable scientific works.